Nonlinear optical response of photochromic azobenzene-functionalized self-assembled monolayers1. Issue 27 (21st July 2015) - Schulze, Michael; Utecht, Manuel; Moldt, Thomas; Przyrembel, Daniel; Gahl, Cornelius; Weinelt, Martin; Saalfrank, Peter; Tegeder, Petra
<x xml:space="preserve">Abstract</x> Incorporating photochromic molecules into organic–inorganic hybrid materials may lead to photoresponsive systems. In such systems, the second-order nonlinear properties can be controlled via external stimulation with light at appropriate wavelengths.